2001
DOI: 10.3402/fnr.v45i0.1801
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acid formation at fermentation of indigestible carbohydrates

Abstract: Short chain fatty acids (SCFAs; acetic, propionic and butyric acid) are formed during bacterial fermentation of carbohydrates in the colon. The interest in SCFA production is related to an increasing body of knowledge of the physiological effects of these acids. SCFAs are important anions in the colonic lumen and serve locally as nutrients for the mucosa cells, stimulating mucosal proliferation and blood flow. Especially butyric acid has been cmphazised. It is the main energy substrate for the colonocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 53 publications
3
48
0
2
Order By: Relevance
“…SCFAs, primarily acetate, propionate and butyrate, are the end-products of microbial fermentation of carbohydrate in the large intestine which depends on the species, amounts of microflora present in the colon, substrate sources and transit time (Wong et al 2006). Different types of non-digestible carbohydrate have been shown to produce different SCFA ratios (Berggren et al 1993;Henningsson et al 2001). Several studies have shown that the acids plays a significant role in the process of inhibiting colon carcinogenesis by stimulating cell proliferation and inducing apoptosis, which in turn affects carcinogenesis (Ruemmele et al 2003;Fung et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs, primarily acetate, propionate and butyrate, are the end-products of microbial fermentation of carbohydrate in the large intestine which depends on the species, amounts of microflora present in the colon, substrate sources and transit time (Wong et al 2006). Different types of non-digestible carbohydrate have been shown to produce different SCFA ratios (Berggren et al 1993;Henningsson et al 2001). Several studies have shown that the acids plays a significant role in the process of inhibiting colon carcinogenesis by stimulating cell proliferation and inducing apoptosis, which in turn affects carcinogenesis (Ruemmele et al 2003;Fung et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20 to 60 g of ingested carbohydrates escape digestion and absorption in the human small intestine each day and enters the colon as a potential source for fermentation (203). These carbohydrates are converted by colonic bacteria to volatile fatty acids (VFAs).…”
Section: Small Intestine Functional Hyperemia (Postprandial Hyperemia)mentioning
confidence: 99%
“…The major VFAs present in the colon are acetic, propionic, and butyric acids. While the relative proportion of VFAs produced from fermentation in the colon vary with the amount and type of indigestible carbohydrate consumed and the colonic microflora, acetate is generally the major anion generated, accounting for about 60% of the total VFA produced (203). It has been reported that intracolonic placement of acetic acid, at physiologically relevant concentrations, increases local colonic blood flow, while butyric, or propionic acids are without effect (286).…”
Section: Small Intestine Functional Hyperemia (Postprandial Hyperemia)mentioning
confidence: 99%
“…In this issue, fermentation is reviewed by Henningsson et al with emphasis on short-chain fatty acid formation (18). Langkilde (19) provides data on available substrates, based on ileostomy studies.…”
Section: Fermentationmentioning
confidence: 99%